Restauration écologique et processus de patrimonialisation des rivières dans l’Ouest de la France - Marie-Anne Germaine (Éditions en environnement VertigO, 2013)
The adoption of the EU Water Framework Directive and the evolution of French water policy involves a multiplication of ecological restoration projects in all valleys. It concerns dam removal and maintain of wild landscape. At local scale, we observe conflicts which illustrate the diversity of landscape and nature representations. River users defend the preservation of different heritages (natural heritage vs. cultural heritage, biodiversity vs. landscape …). From the example of river restoration projects which we have studied in north western France, we purpose to identify rivers heritage conservation’s values and process. The study is based on local conflicts analysis and water local governance difficulties.